2001
DOI: 10.1002/1521-4095(200108)13:15<1158::aid-adma1158>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Two-Dimensional Arrays of Ferrite Nanoparticles

Abstract: Uniform 2D arrays of organically passivated magnetite (Fe3O4) and cobalt ferrite (CoFe2O4) have been prepared by the Langmuir–Blodgett technique. Preliminary studies of the magnetization curves show small changes in the shape of the curves depending on the number of deposited layers. Control over the formation of the colloidal solutions and of the 2D arrays, combined with the possibility to tune the physical properties of these arrays, may lead to new information storage media as well as novel magnetoresistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
264
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(274 citation statements)
references
References 7 publications
6
264
1
3
Order By: Relevance
“…In order to overcome these difficulties, nanometer size reactors for the formation of homogeneous nanoparticles of cobalt ferrite are used. To protect the oxidation of these nanoparticles from the atmospheric oxygen and also to stop their agglomeration, the particles are usually coated and dispersed in some medium like sodium dodecyl sulfate (NaDS) or oleic acid [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these difficulties, nanometer size reactors for the formation of homogeneous nanoparticles of cobalt ferrite are used. To protect the oxidation of these nanoparticles from the atmospheric oxygen and also to stop their agglomeration, the particles are usually coated and dispersed in some medium like sodium dodecyl sulfate (NaDS) or oleic acid [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…According to Cheng et al, 2005; the in vitro cytotoxicity test revealed that the magnetite particles exhibited excellent biocompatibility. Fe 3 O 4 nanoparticles are commonly produced via co-precipitation of Fe(II) and Fe(III) ions by a base, usually sodium hydroxide or aqueous ammonia (Kang et al, 1996;Hong et al, 1997;Fried et al, 2001) or they may be made by thermal decomposition of alkaline solution of Fe(III) chelate in the presence of hydrazine and by sonochemical decomposition of hydrolyzed Fe(II) salt followed by thermal treatment (Sapieszko et al, 1980;Vijayakumar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 In particular, that one can produce nanoparticles with a very narrow size distribution, or the so-called monodisperse, and in high reproducibility [3][4][5][6] rendered it possible to focus on their more intrinsic properties and associated applications. 7,8 In most prospective applications, nanoparticles are used as in solutions or nanopowders.…”
mentioning
confidence: 99%